Meta analysis of the prevalence of subclinical mastitis in dairy cattle - Çelik Gürbulak, E; Akçay, A (Journal of the Hellenic Veterinary Medical Society, 2024)
Mastitis, which is defined as the inflammation of mammary tissue caused by infectious agents such as bacteria, yeast, fungi and viruses, is considered to be one of the most important problems of dairy enterprises due to reduced milk yield and milk quality. Therefore, studies on mastitis have been continuous from past to present. The presence of too many studies conducted in all around the world in order to estimate the prevalence of mastitis and to determine the factors affecting the disease has necessitated systematic review or meta-analysis studies on this subject. In this study, it was aimed to perform the meta-analysis for the prevalence of cow and udder quarter-based subclinical mastitis in 193 studies conducted around the world, and to determine the effects of some factors on the prevalence of subclinical mastitis using subgroup and meta-regression methods. Because high heterogeneity was detected between studies in the analysis, the random effects model (Der Simonian-Laird method) (Q=15149.869, df=188, p<0.001, I2=98.759; Q=72142.706; df=174, p<0.001; I2=99.774) was used in this study. The publication biases in the study samples were determined by the use of Egger’s linear regression test, the Begg and Mazumdar rank correlation test and funnel plots. As a result of the study, the common prevalence of subclinical mastitis in cow and udder quarter-based studies were calculated as 0.46 (95% CI: 0.43-0.48) and 0.32 (95% CI: 0.30-0.34) respectively. The meta-analysis conducted in this study has enabled the elimination of inconsistencies in the prevalence of subclinical mastitis in individual studies conducted around the world, and has provided a stronger and more precise estimate.